Insights about the publicness of public space from the Kamppi area of Helsinki - Tamašauskaitė, Žieda (Geographical society of Finland, 2025)
Undergoing dramatic changes in its form, structure and purpose, public space has recently drawn sharp criticisms from its investigators and its theorists. At the same time, for the public who use it, public space has continued to be meaningful and attractive. To understand what public space is and what constitutes its publicness in the city of today, I conducted a multiple-case study and prepared a doctoral dissertation Publicness of Public Space in the Contemporary City: Insights from Helsinki (Tamašauskaitė 2024). On March 1st, 2024, during the public defence of my dissertation, I gave a lectio praecursoria, which this short article is based on. In my lectio, I overviewed contestations over the concepts public space and publicness, suggesting that the publicness of contemporary public space shall be conceived through use and treated as a phenomenon that comprises three dimensions, namely activities, users and control. The focus of the lectio was on my main findings from the three publicly usable spaces within the Kamppi area of Helsinki: Narinkka Square, Tennispalatsi Square and Kamppi Shopping Centre. First, I highlighted that from my study, I learnt that the publicness of the three spaces is primarily activity-based, whereby their publicness is strikingly similar when the spaces are used in comparable ways. Next, I suggested that even if the diversity of user groups is highly important in ensuring a wide variety of activities, it is all those activities that intermix and combine with one another that produces an ecosystem out of activities and that reveal the dynamics of activity-based publicness to be situational. Finally, I argued that various means of control are but some of the matters that affect the actual and the possible use of public space, for the publicness of adjacent public spaces may also complement each other.